On property deconvolution from indentation of coated systems - Korsunsky, A; Constantinescu, A (2015)
In many situations in industry problems of achieving optimal service properties are best solved by using surface engineering techniques, e.g. by deposition of thin coating layers on the existing substrate. In most such situations the problem of property identification arises, initially in the context of fitness-for-purpose characterization of the resulting system, then in connection with process optimisation in order to achieve best performance, and finally in the context of in-service degradation and lifetime prediction. In all cases, reliable and yet cost-efficient determination of the mechanical properties of all components is crucial. We present an overview of the model response function approach to the characterisation of coated systems by indentation. Both elastic and inelastic (plasticity or fracture) modes of response are considered, and the use of a uniform fitting approach is demonstrated. For validation, a range of experimental data on system hardnes and contact modulus is used, along with numerical models of the indentation process using elasto-plastic finite element solutions and integral equation inversion for the frictionless elastic contact problem.